2017
DOI: 10.1089/ars.2016.6633
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Evaluated Cancer Drugs Inhibiting Redox Signaling

Abstract: Significance: There are a number of redox-active anticancer agents currently in development based on the premise that altered redox homeostasis is necessary for cancer cell's survival. Recent Advances: This review focuses on the relatively few agents that target cellular redox homeostasis to have entered clinical trial as anticancer drugs. Critical Issues: The success rate of redox anticancer drugs has been disappointing compared to other classes of anticancer agents. This is due, in part, to our incomplete un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 105 publications
(85 reference statements)
1
34
0
2
Order By: Relevance
“…Conversely, we found that REDD1-deficient tumors are highly sensitive to glutathione depletion with BSO. Clinical trials using this agent have not yielded responses in a large proportion of tumors, yet our findings suggest the possibility that targeting a metabolically defined tumor subset, such as that discovered here, may be more successful (Kirkpatrick and Powis 2017). Finally, CD36 itself is an attractive potential therapeutic target whose inhibition has proven relatively nontoxic in preclinical models (Pascual et al 2017).…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, we found that REDD1-deficient tumors are highly sensitive to glutathione depletion with BSO. Clinical trials using this agent have not yielded responses in a large proportion of tumors, yet our findings suggest the possibility that targeting a metabolically defined tumor subset, such as that discovered here, may be more successful (Kirkpatrick and Powis 2017). Finally, CD36 itself is an attractive potential therapeutic target whose inhibition has proven relatively nontoxic in preclinical models (Pascual et al 2017).…”
Section: Discussionmentioning
confidence: 76%
“…Here we have shown that Tat induced mitochondrial ROS. New generation of antioxidants specifically targeting mitochondria is currently being developed [114] , [115] , [116] . Their use may allow for further advances in understanding the processed involved in HIV-induced oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Those results support the idea that cancer cells might evolve resistance mechanisms in other antioxidant pathways in order to counteract oxidative stress, thus being able to survive. In a clinical context, BSO was shown to be a chemosensitizer but with no clinical advantages due to the severe adverse effects, thus clinical trials are no longer being developed [ 63 ].…”
Section: Gsh Antagonists In Ovarian Cancermentioning
confidence: 99%
“…Telcyta (TLK286) is a GSH analogue that, when metabolized by GSTP1-1, releases a reactive tetrakis (chloroethyl) phosphorodiamidate fragment and a glutathione analogue vinyl sulphone that, following activation, triggers the stress response pathway, leading to cellular apoptosis induction [ 69 ]. Telcyta has been tested in Phase II and III clinical trials for ovarian cancer treatment, as a monotherapy regime or in combination with other chemotherapeutic agents [ 63 ]. However, a Phase III (NCT00350948) randomized study of Telcyta and doxorubicin in platinum refractory ovarian cancer patients (ASSIST-5) showed that Telcyta led to poorer outcomes than standard strategies [ 63 ].…”
Section: Gsh Antagonists In Ovarian Cancermentioning
confidence: 99%